2004
DOI: 10.1111/j.1365-2109.2004.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility of selected ingredients in diets for juvenile grouper, Epinephelus coioides (Hamilton)

Abstract: Apparent digestibility coe⁄cients (ADCs) for dry matter (ADC dm ) and crude protein (ADC cp ) of selected feed ingredients were determined in vivo for grouper using passive faeces collection (Guelph System). A reference diet (RF) and test diets (consisted of 70% RF and 30% test ingredient) with 1% Cr 2 O 3 as an inert indicator were used. An RF contained 45% protein, 10% fat and 15.7 kJ g À1 metabolizable energy. Three isonitrogenous and isocaloric diets, each contained a test ingredient (white ¢sh meal, white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 24 publications
3
33
0
1
Order By: Relevance
“…Fish are unable to make use of phytate-nutrient complexes because they lack the enzyme phytase (Riche et al, 2001). Tannins hinder the digestive process by binding to digestive enzymes such as protease resulting in a decrease in proteolytic enzyme activity, leading to reduced protein digestibility (Eusebio et al, 2004). Tannins also decrease the absorption of essential vitamins (Francis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish are unable to make use of phytate-nutrient complexes because they lack the enzyme phytase (Riche et al, 2001). Tannins hinder the digestive process by binding to digestive enzymes such as protease resulting in a decrease in proteolytic enzyme activity, leading to reduced protein digestibility (Eusebio et al, 2004). Tannins also decrease the absorption of essential vitamins (Francis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The poor performance (growth, protein utilisation and digestibility) of fish fed MM diets may be attributed to the negative effects of anti-nutrients. According to Eusebio et al (2004) the presence of anti-nutrients may hinder the digestibility and utilisation of dietary nutrients. Phytate reduces the bioavailability of nutrients due to formation of complexes such as a phytate-mineral/protein complex.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Wilson and Poe (1985) reported that the channel catfish, an omnivorous species with clear preference for APs, can digest in excess of 70% of raw starch gross energy contents. Dietary plant ingredients can affect gastrointestinal transit time of feed as a result of the presence of fibres and sugars, and alter the digestibility of nutrients ingested by the fish (Storebakken et al, 1999;Eusebio et al, 2004;Zhou et al, 2004). According to Eusebio et al (2004), as dietary fibre is part of the carbohydrate component of plant ingredients, most fish cannot utilize it.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary plant ingredients can affect gastrointestinal transit time of feed as a result of the presence of fibres and sugars, and alter the digestibility of nutrients ingested by the fish (Storebakken et al, 1999;Eusebio et al, 2004;Zhou et al, 2004). According to Eusebio et al (2004), as dietary fibre is part of the carbohydrate component of plant ingredients, most fish cannot utilize it. However, low dietary concentrations of dietary fibre (3-5%) may have a beneficial effect on fish growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation